1991
DOI: 10.1002/j.1537-2197.1991.tb11432.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Senescence of Cortical Cells in the Roots of Cereals. How Good Is the Evidence?

Abstract: There are numerous reports that cortical cells senesce in young, otherwise healthy main roots of cereals, including com. These are based on apparent absence of nuclei in root segments or transverse sections after acridine-orange staining. Senescence is said to progress from the outer to the inner cortex basipetally from the root tip, except cells around branch bases where nuclei always stain. We studied axile roots of soil-grown cereals using various methods to detect nuclei primarily in longitudinal sections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…This is in accord with the results of Wenzel and McCully (1991) who did not find enucleated and early senescing cells in longitudinal sections of intact maize, wheat, barley and oat roots. This is in accord with the results of Wenzel and McCully (1991) who did not find enucleated and early senescing cells in longitudinal sections of intact maize, wheat, barley and oat roots.…”
Section: Resultssupporting
confidence: 93%
“…This is in accord with the results of Wenzel and McCully (1991) who did not find enucleated and early senescing cells in longitudinal sections of intact maize, wheat, barley and oat roots. This is in accord with the results of Wenzel and McCully (1991) who did not find enucleated and early senescing cells in longitudinal sections of intact maize, wheat, barley and oat roots.…”
Section: Resultssupporting
confidence: 93%
“…The main problems are associated with focusing the microscope on cell layers deep in the cortex and the need to account for the curvature of the root surface. The latter explanation is most consistent with the observations of intact nuclei and cytoplasmic streaming in cells whose nuclei failed to stain (Wenzel and McCully, 1991). Liljeroth (1995) overcame some of these problems by freezing the root, cutting it in half longitudinally, and examining the cut surface.…”
Section: Discussionsupporting
confidence: 66%
“…Defoliation and infection by foliar pathogens has little effect on the rate of loss, but shading can reduce it (Deacon and Mitchell, 1985;Lascaris and Deacon, 1991b). More recently, the loss of stainable nuclei in wheat and barley has been associated with an increase in DNA fragmentation as shown by an in situ TUNELassay (Liljeroth and Bryngelsson, 2001 Although the above evidence suggests that changes are taking place within the root cortex as the tissue ages, the acridine orange staining technique used has been criticized and the conclusion that nuclei are lost before cell death has been challenged (Wenzel and McCully, 1991). Using Nomarski optics, these authors were able to find intact nuclei and cytoplasmic streaming in cells of whole tissues and tissue macerates that failed to stain with fluorescent dyes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H o w e v e r , there are s i g n i f i c a n t structural changes in seminal root tissue with ageing. Wenzel and McCully (1991) reported that parts of the cortices of seminal roots of 28day old wheat plants are sloughed off in soil-grown plants. A comparison of nitrate uptake between basal and apical segments from roots of older plants might yield different results from those of this study.…”
Section: Resultsmentioning
confidence: 99%